Utility of pre-operative abdominal ultrasound to predict conversion to open cholecystectomy - Sharma, Reetesh; Dumbre, Ramesh; Fernandese, Arun; Phalgune, Deepak (International Surgery Journal, 2021)
Background: Many factors like unclear Calot triangle anatomy, intensely inflamed and thick gallbladder, dense adhesions in the operative area, obscure biliary tree anatomy, local inflammation like pancreatitis contribute to the conversion of laparoscopic cholecystectomy to open cholecystectomy. The aim of the present study was to find the utility of abdomen sonography parameters that predict the conversion from laparoscopic to open cholecystectomy. Methods: Ninety patients aged between 20 and 75 years with the diagnosis of cholelithiasis/cholecystitis were included in this observational study. Every patient underwent ultrasonography (USG). The USG findings such as gallbladder wall thickness, presence or absence of stones, number of calculi, size of the calculi, presence of abdominal adhesions, size of the common bile duct was recorded. If feasible, laparoscopic cholecystectomy was done. If not, the procedure was converted to open cholecystectomy. Association of USG findings was correlated with conversion to open cholecystectomy. The comparison of the qualitative variables was done using Fisher’s exact test. Results: Of 90 patients, 7 (7.8%) had a conversion to open cholecystectomy. There was no statistically significant difference of USG parameters studied such as gallbladder wall thickness >4 mm, pericholecystic fluid collection, common bile duct diameter >7 mm, presence of calculus, number of calculi, size of calculus >6 mm and adhesions/fibrosis in patients who required conversion to open cholecystectomy and who were operated laparoscopically. Conclusions: Pre-operative USG parameters did not predict conversion to open cholecystectomy.